Inovasi Pelayanan Publik Dalam Penyediaan Aplikasi LAPAKAMI - sari, annisa ratna; Pamungkas, Bambang; Setiawan, Erwin; Santa, Rahmat (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Technological advances have had a positive impact on the implementation of e-government in internet-based service innovation at the central to local government levels. One example is the LAPAKAMi application issued by the Cimahi City Government through the Cimahi City Communication and Information Service. The research method used in this study is a qualitative method. This research will involve collecting data and information collected through reviewing research journals, literature, as well as visual sources through images and videos sourced from the YouTube application (Sugiono 2019). This article will analyze how the LAPAKAMi application has provided convenience in public services. Through this application, the public can easily access information and carry out various transactions with local governments. For example, the public can apply for permits, report complaints, or obtain information related to other public services. With the LAPAKAMi application, the public service process becomes more efficient and transparent. People no longer need to visit government offices in person, but can access services online through this application. This also helps reduce bureaucracy and speed up the resolution of various requests or complaints. Apart from that, the LAPAKAMi application also allows local governments to collect more accurate and up-to-date data and information. This makes it easier to make decisions and plan development at the local government level.